Effect of verbascoside on decreasing concentration of oxygen free radicals and lipid peroxidation in skeletal muscle - Li Jing-xiang; Xing Dong; Li Hui; Lu Jing-fen; Tong Christopher Wai-chung; Gao Jian-nian; Chan Kai-ming (Acta Pharmacologica Sinica, 2016)
AIM: To detect the effects of verbascoside on decreasing the concentration of oxygen free radicals (OFR) and lipid peroxidation in skeletal muscle resulting from exhaustive exercise. METHODS: Electron spin resonance (ESR) technique and thiobarbituric acid reaction (TBAR) method were used to detect the concentration of OFR in intact gastrocnemius muscle and the contents of milondialdehyde (MDA) in muscle homogenate. RESULTS: Verbascoside decreased the concentration of OFR (P < 0.05) and the level of lipid peroxidation (P < 0.05) in muscle caused by exercise. CONCLUSION: Verbascoside has the effects of reducing oxidative stress in muscle caused by exhaustive exercise by decreasing the concentration of free radicals and the level of lipid peroxidation.